2015
DOI: 10.1103/physrevc.92.034905
|View full text |Cite
|
Sign up to set email alerts
|

Cancellation of theσmeson in thermal models

Abstract: The by now well-established scalar-isoscalar resonance f0(500) (the σ meson) seems potentially relevant in the evaluation of thermodynamic quantities of a hadronic gas, since its mass is low. However, we recall that its contribution to isospin-averaged observables is, to a surprising accuracy, canceled by the repulsion from the pion-pion scalar-isotensor channel. As a result, in practice one should not incorporate f0(500) in standard hadronic resonance-gas models for studies of isospin averaged quantities. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 44 publications
5
82
0
Order By: Relevance
“…As pointed out in Ref. [22], the inclusion of this channel partly cancels the effect of the isospin I = 1/2 channel. This is expected since the phase shift in the I = 3/2 channel, and consequently the weight function B I=3/2 (M ), are negative, corresponding to a repulsive interaction.…”
Section: The Effect Of I = 3/2 Kπ Scatteringmentioning
confidence: 64%
“…As pointed out in Ref. [22], the inclusion of this channel partly cancels the effect of the isospin I = 1/2 channel. This is expected since the phase shift in the I = 3/2 channel, and consequently the weight function B I=3/2 (M ), are negative, corresponding to a repulsive interaction.…”
Section: The Effect Of I = 3/2 Kπ Scatteringmentioning
confidence: 64%
“…Some recent studies indicate that its effect is crucial in some particular observables regarding CSR [357], whereas the effect of the σ has also been shown to compensate largely with the isospin 2 channel for other observables like scalar susceptibilities [362] . Actually this cancellation between the isoscalar and isotensor channels in hadron resonance gases was already found in [363] and in view of the present parameters of 116 the f 0 (500) meson it has been suggested that the sigma meson should not be included in Hadron Resonance Gas models (unless the isotensor wave is included too), as long as one is interested in isospin-averaged observables [364]. Furthermore, if the sigma is implemented and the low energy part is important for a given observable, we have shown in previous sections that the simplest LσM, which is the model most widely used for this purposes, is insufficient to describe our present knowledge.…”
Section: The σ Meson and Chiral Symmetry Restorationmentioning
confidence: 99%
“…The σ implemented as a Breit-Winger pole with M σ = 484 and Γ σ /2 = 255 MeV produces up to 5% of pions, while the truth contribution is −0.3%, see Fig. 5 (right) [31]. The absence of pions from the σ decays enhances all ratios to pions, compared to the results that were obtained in models with σ.…”
Section: Icnfp 2015mentioning
confidence: 63%
“…The attractive one is responsible for the emergence of the f 0 (500) resonance, however, the repulsive one cancels f 0 (500) until f 0 (980) takes over above the mass M ππ ∼ 0.85 GeV, see Ref. [31]. The cancellation happens on the level of the distribution function, therefore it is present in all isospin-averaged observables.…”
Section: Icnfp 2015mentioning
confidence: 98%